The Phenomenon of Bullying in Schools during the COVID-19 Pandemic: A Quranic Perspective - Mela, Lita; Musthofa, Tulus (Dialogia, 2023)
Bullying is still common in the education sector, especially in online learning during the COVID-19 pandemic. Bullying between students in online learning occurs verbally through social media. In contrast, in offline learning, bullying is carried out as evasion and exclusion in the school environment, such as canteens, toilets, classrooms, and parking lots. This study aims to discuss bullying in schools from the perspective of the Qurán. This study uses a qualitative method, with the type of library research, the historical approach, and the descriptive approach used. Bullying from the perspective of the Qur'an can be seen from the prohibition of bullying behavior in surah Al-Hujurat verse 13 and surah Yusuf verses 8-10. Meanwhile, solutions for victims and bullying behavior can be seen in the Al-Qur'an surah Al-Luqman verses 13-19, At-Thaha verses 132, and Ash-Shura verses 39-43.